KOREAN SHAMANISM – THE RELIGION OF WOMEN - OH, Kyong-geun (International Journal of Korean Humanities and Social Sciences, 2016)
Shamanism is one of the oldest religions that have existed around the world. But Korean shamanism is very exceptionally in the world, because it is monopolized by women. This article focuses on the main reasons for that state of affairs. Korean shamanism has never been accepted by the ruling class as an official religion. It was not supported by the elites of the society, so it has functioned only at the margin of culture and society. Confucian-patriarchy in the Joseon dynasty (1392-1897) was one of the main reasons why Korean shamanism became the religion of women. According to Confucian ideology there must be sexual segregation in the household, and it was extended even to ritual performances for the gods. Men satisfied their religious needs through Confucianism, but they completely excluded women from it. As women were excluded from Confucian ceremonies they needed to find a religion for themselves. The gods worshiped in shamanism and the shamanistic ritual itself were treated by the ruling class as coarse and vulgar, suitable only for people of lower classes and women. The gods in Korean shamanism are not providing people with noble ideals or dreams, they just support human beings by protecting them against bad luck and bringing them good luck. A Korean shamanistic ritual consists mainly of dances and singing. Shamans communicate with their gods in a trance induced by dancing vigorously. In the Joseon dynasty dominated by Confucian ideology it was very unsuitable for men.